2010
DOI: 10.1177/0300985810369901
|View full text |Cite
|
Sign up to set email alerts
|

Increased Presence of Stromal Myofibroblasts and Tenascin-C With Malignant Progression in Canine Mammary Tumors

Abstract: The aims of this study were to determine whether the appearance of stromal myofibroblasts and the expression of tenascin-C (Tn-C) correlate with the grade of malignancy in canine mammary tumors and to determine the main cellular source of Tn-C in these tumors. Single or double immunostaining using antibodies against a-smooth muscle actin (a-SMA) and Tn-C was performed on serial sections of normal canine mammary glands as well as those with lobular hyperplasia, simple adenoma, and simple carcinoma. Thirty-nine … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
27
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 25 publications
(31 citation statements)
references
References 35 publications
4
27
0
Order By: Relevance
“…Importantly, we could further validate our observations by an IHC analysis of αSMA protein levels, which were significantly upregulated in stromal cells of the tumour but not in normal stroma ( Figures 3A, 4A and 5A). This finding is consistent with another report demonstrating an increase in aSMA immunoreactivity in stroma of canine simple mammary carcinomas [48]. The specific localisation of staining with αSMA to CAS but not normal stroma or neoplastic epithelial cells further underlined the specificity of our approach in isolating CAS and normal stroma by LCM.…”
Section: Acta2/αsmasupporting
confidence: 92%
“…Importantly, we could further validate our observations by an IHC analysis of αSMA protein levels, which were significantly upregulated in stromal cells of the tumour but not in normal stroma ( Figures 3A, 4A and 5A). This finding is consistent with another report demonstrating an increase in aSMA immunoreactivity in stroma of canine simple mammary carcinomas [48]. The specific localisation of staining with αSMA to CAS but not normal stroma or neoplastic epithelial cells further underlined the specificity of our approach in isolating CAS and normal stroma by LCM.…”
Section: Acta2/αsmasupporting
confidence: 92%
“…The higher proportion of stroma in the true SSC could possibly reflect the potential for greater infiltration, because tumor stroma is most likely related to tumor progression. 11 Our previous study indicated that the appearance of stromal myofibroblasts is associated with poor prognosis for canine mammary simple carcinoma.…”
mentioning
confidence: 96%
“…3) The use of 'intraepithelial' means that these pathologies are independent of their immediate environment; however, as recent research demonstrates, the stroma has a more significant role in the evolution of these lesions than previously acknowledged [20,[46][47][48][49][50][51][52][53][54]. Our own research in canines clearly shows that these pathologies are accompanied by significant (and to some extent are dependent on) changes starting in early development not only of myoepithelial cells but also their surrounding microenvironment, which includes the basal membrane, the amount of connective tissue and the infiltration of leukocytes [19,[55][56][57][58][59][60][61][62][63][64][65][66][67].…”
Section: Discussionmentioning
confidence: 99%